Psychological processes in chronic pain: influences of reward and fear learning as key mechanisms : behavioral evidence, neural circuits, and maladaptive changes - Nees, Frauke; Becker, Susanne (Neuroscience, 2018)
In the understanding of chronic pain, hypotheses derived from psychological theories, together with insights from physiological assessments and brain …